The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3ma00505d
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing a carbon-based material from food waste digestate for dye adsorption: the role of hydrogel beads in enhancing the material stability and regenerative capacity

Salaheddine Farsad,
Asma Amjlef,
Ayoub Chaoui
et al.

Abstract: This study has been focused on both the ecologic and the economic gains resulting from the food waste treatment. Accordingly, anaerobic digestion and adsorption were combined to solve these problems,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…25 Groundwater can be contaminated by chemical fertilizers containing nitrogen, phosphate, and potassium. 26,27 Nitrate-based fertilizers are responsible for methemoglobinemia, which can damage the respiratory and circulatory systems. Studies have shown the impact of chemical fertilizers on water, soil, and air pollution.…”
Section: Advantages and Disadvantages Of Chemical Fertilizers And Nan...mentioning
confidence: 99%
“…25 Groundwater can be contaminated by chemical fertilizers containing nitrogen, phosphate, and potassium. 26,27 Nitrate-based fertilizers are responsible for methemoglobinemia, which can damage the respiratory and circulatory systems. Studies have shown the impact of chemical fertilizers on water, soil, and air pollution.…”
Section: Advantages and Disadvantages Of Chemical Fertilizers And Nan...mentioning
confidence: 99%
“…The role of initial pH in practical applications is crucial to the degradation of organic pollutants. To this end, various pH tests in a range of (3)(4)(5)(6)(7)(8)(9)(10)(11) were conducted on the CoCN-NaBH 4 /PMS system, as depicted in Fig. 9d.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Undoubtedly, the issue of organic dye pollution is becoming an increasing environmental hazard. [1][2][3] Such pollution results from the intensive development of chemical industries, which is the primary culprit behind the environmental degradation by organic dye pollutants. [4][5][6][7][8] In the last few years, numerous scientific papers have been published with the aim of finding solutions to this environmental contamination problem.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes released from industrial activities pose a threat to both aquatic ecosystems and human health. 1,2 Consequently, the development of effective and sustainable strategies for the removal of these contaminants is of paramount importance. [3][4][5][6] Peroxymonosulfate based advanced oxidation processes (AOPs) have emerged as a promising technique for the degradation of organic contaminants due to the versatility, longer half-life (t 1/2 = 30-40 ms), and strong oxidizing potential (2.5-3.1 V) of sulfate radicals.…”
Section: Introductionmentioning
confidence: 99%